2020
DOI: 10.1007/s10660-020-09432-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of product distance on the eWOM in recommendation network

Abstract: The online Product Recommendation Networks (PRNs), connecting similar products with hyperlinks, have been widely implemented in user-generated content websites and ecommerce systems. With the PRNs as the virtual shelves, this paper explores the impact of the distance between products on the formation of product electronic Word-of-Mouth (eWOM). Employing an empirical book recommendation network of Amazon, the study one explores the effect of a focal product's neighborhood (nearby others) on its eWOM, and study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…They have access to a greater amount of information and can influence the opinion of others through their connections. It has also been found [6] that users who are part of high-density networks are more likely to be influenced by the positive or negative opinions and reviews of other users. The current research focuses on the influence of social network centrality and density on users' tendency to post positive or negative reviews about products or services, known as electronic Word of Mouth (eWOM).…”
Section: Introductionmentioning
confidence: 99%
“…They have access to a greater amount of information and can influence the opinion of others through their connections. It has also been found [6] that users who are part of high-density networks are more likely to be influenced by the positive or negative opinions and reviews of other users. The current research focuses on the influence of social network centrality and density on users' tendency to post positive or negative reviews about products or services, known as electronic Word of Mouth (eWOM).…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that recommender systems are vulnerable to malicious profile injections, which are also known as the shilling attacks [13]. With a large number of skewed ratings, injected fake user profiles can mislead the recommender system in measuring similarities [19] [29]. As a result, attackers can manipulate the recommendation results for their intended commercial interests.…”
Section: Introductionmentioning
confidence: 99%